Transformative Study of The A’Bulo Sibatang-Based Rational-Moral Decision Framework as a Conflict Resolution Approach to Peaceful School - Asmaul Husnah Amiruddin; Bustan Bustan (Institut Teknologi Pendidikan Indonesia, 2026)
Conceptualization of conflict resolution in schools often falls into short-term and coercive behaviorist approaches, failing to build sustainable peace. This study aims to construct a theoretical framework integrating modern rational-moral reasoning with the local wisdom values of A’Bulo Sibatang in conflict resolution toward a Peaceful School. The method employed is qualitative research through conceptual research with a conceptual-philosophical analysis approach. Secondary data from theoretical literature texts were descriptively analyzed using content analysis techniques through reduction, categorization, and conceptual synthesis phases. The results indicate that the integration between rational-moral reasoning (Terry, Fraenkel, and Rest Models) and Bugis-Makassar local wisdom of A’Bulo Sibatang (Sipakatau, Sipakainge, Assamaturukang) successfully shifts the conflict resolution paradigm from individual-egocentric to communal-inclusive. Operationally, students' cognitive restructuring process is mapped through Rest's four moral components that run align with Coleman's cooperative conflict resolution indicators. The study concludes that the downstreaming of this conceptual-epistemological integration generates a local wisdom-based value learning model capable of reconstructing schools into social laboratories and conducive multicultural education spaces. Theoretically, the internalization of these collaborative values is proven to provide psychological well-being, strengthen solidarity among school members, and ensure the sustainability of inclusive social harmony in institutionalizing the Peaceful School ecosystem.